Management system of an active genebank of common bean Sistema gerenciador de banco ativo de germoplasma de feijão - Coan M.M.D.* (2010)
Genetic resources are conserved ex situ in genebanks, which are used as a source of useful alleles. The information generated by the Active Common Bean Genebank (ACBG) is stored in a Database Management system which ensures a quick and safe data recovery. Using Microsoft Access, a database system was developed to store and search bases of accession combinations or directly among morphological, physiological and yield descriptors of common bean. The system called Common Bean Genebank (CBGB) provides a graphical interface for the operation in the database, facilitating and optimizing the search time in germplasm catalogues.